Implementation of Cloud Computing for SOS Application Back-End using Google Cloud Platform - Firdonsyah, Arizona; Indah, Mahrunisa (Sinkron : jurnal dan penelitian teknik informatika, 2025)
This research discusses the implementation of cloud computing on the Backend of the SOS application using the Google Cloud Platform. The background of the research is based on the high crime rate in Indonesia, especially theft cases which reached 3396 cases in the period August-September 2024. The purpose of the research is to develop an application that can help users in emergency situations by providing information on the location of the nearest police station within a maximum radius of 5 KM. The method used is Agile Kanban, which was chosen because of its flexible nature and emphasizes rapid response to change. The Backend implementation uses Google Cloud Platform services including Maps API (Places API, Geocoding API, and Distance Matrix API) for location features, and Google Firestore for data storage. The results of the research show that the implementation of cloud computing for the Backend of the ResQHub application successfully displays the location of the nearest police station from the user, but there are still obstacles in the integration of Firestore for storing user data and signup/login authentication. Further research will focus on frontend development for mobile implementation and completion of Firestore integration.